2014
DOI: 10.1183/09031936.00001414
|View full text |Cite
|
Sign up to set email alerts
|

Microgravity and the respiratory system

Abstract: The structure of the lung, with its delicate network of airspaces and capillaries, means that gravity has a profound influence on its function. Studies of lung function in the absence of gravity provide valuable insight into how, for we Earth-bound individuals, its unavoidable effects shape our lung function. Gravity causes uneven ventilation in the lung through the deformation of lung tissue (the so-called Slinky effect), and uneven perfusion through a combination of the Slinky effect and the zone model of pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 79 publications
(91 reference statements)
1
42
0
2
Order By: Relevance
“…However, if the string is stretched further (to simulate inspiration), and due to the elastic recoil forces of the spring, the loops in the lower part of the spring are more distant apart from each other than in the upper part (and by comparison, ventilation is greater in the lower parts of the lung). If the effects of gravity are removed, this model would predict uniform alveolar size, ventilation and perfusion (122). …”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, if the string is stretched further (to simulate inspiration), and due to the elastic recoil forces of the spring, the loops in the lower part of the spring are more distant apart from each other than in the upper part (and by comparison, ventilation is greater in the lower parts of the lung). If the effects of gravity are removed, this model would predict uniform alveolar size, ventilation and perfusion (122). …”
Section: Animalsmentioning
confidence: 99%
“…In summary, “gravity causes uneven ventilation in the lung through the deformation of lung tissue (Slinky effect), and uneven perfusion through a combination of the Slinky effect and the zone model of pulmonary perfusion” (122). …”
Section: Animalsmentioning
confidence: 99%
“…Despite the fact that an early murine model study [19] identified that anti-orthostatic positioning, which is changing the direction of gravity relative to the body vertical axis, may increase water content in the lungs and reduce the properties of pulmonary surfactant, there appears to be little or no effect on lung function in humans in space [20]. Two areas are, however, worthy of further discussion.…”
Section: Respiratory Systemmentioning
confidence: 82%
“…In the early years of space flight, missions were of the period of days and a very restricted number of medicines were carried, some of which are shown in Table 3 Respiratory function Limit number of EVAs and optimise hyperoxia-inducing regime [20,21] Construct 3D human lung models and characterise lung biomarkers under different conditions. [23] Immune function and infection…”
Section: Use Of Medication In Space-the Early Yearsmentioning
confidence: 99%
See 1 more Smart Citation